Psychosocial adjustment and adaptation in young adults surviving pediatric cancer: A systematic review - Alfonso Rodríguez, Laura; Castellano-Tejedor, Carmina; Blasco Blasco, Tomás (Psicooncología, 2024)
Introduction: Long-term effects of childhood tumors can alter the trajectory of adjustment and psychosocial adjustment of survivors later in life. Purpose: This systematic review focuses on analyzing the experiences of posttraumatic growth, posttraumatic stress, emotional distress, and psychosocial difficulties experienced by young adult survivors of pediatric cancer. Results: The results suggest a more prevalent trajectory that could be conceptualize as adaptive, in which both post-traumatic growth (prevalence greater than 50%) and post-traumatic stress symptoms (prevalence less than 30%) are observed. However, compared to the non-oncology control population, these survivors are at higher risk for anxiety and depressive symptoms, lower educational and occupational attainment, and remaining single or living alone, which is hypothesized to be related to the sequelae of each tumor type and treatment, and not just the disease experience. Conclusions: Care for young adult survivors of pediatric cancer should focus on providing enhanced long-term medical and psychosocial support through an interdisciplinary approach and person-centered care as an approach that supports a trajectory of adaptive adjustment.